Rare plant communities of Kyiv city floodplain meadows (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The meadow vegetation of the Kyiv city waters and its rare communities, which belong to seven associations Agrostio vinealis Calamagrostietum epigei, Festucetum pratensis, Koelerio Agrostietum vinealis, Lysimachio vulgaris Filipenduletum, Agrostio giganteae Fe stucetum pratensis, Poetum pratensis, Poo palustris Alopecuretum pratensis were researched. Iris sibirica from the Red Data Book of Ukraine was found in these communities. It has large projective coverage and constancy in Festucetum pratensis and Lysimachi o vulgaris Filipenduletum . III protection category is proposed to be included into new edition of the Green Data Book of Ukraine. Other five associations need to IV protection category.
Keywords: rare phytocenofond, Green Data B ook of Ukraine, associatio ns, meadows, wealth, biodiversity.